2018
DOI: 10.1038/s41598-018-26408-2
|View full text |Cite
|
Sign up to set email alerts
|

The neurotrophic tyrosine kinase receptor TrkA and its ligand NGF are increased in squamous cell carcinomas of the lung

Abstract: The neurotrophic tyrosine kinase receptor TrkA (NTRK1) and its ligand nerve growth factor (NGF) are emerging promoters of tumor progression. In lung cancer, drugs targeting TrkA are in clinical trials, but the clinicopathological significance of TrkA and NGF, as well as that of the precursor proNGF, the neurotrophin co-receptor p75NTR and the proneurotrophin co-receptor sortilin, remains unclear. In the present study, analysis of these proteins was conducted by immunohistochemistry and digital quantification i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…In the adult, TrkA also acts as a pain receptor in sensory neurons and contributes to the transmission of pain signals to the central nervous system [8]. Outside of neuronal growth and pain signaling, there is an increasing number of studies demonstrating that TrkA tumour-promoting signaling is present in several human cancers, including those of the breast [10], oral cavity [11], thyroid [13], cervix [43] and lung [14,15]. In our study, TrkA protein expression was found preferentially in IDC as compared to DCIS and ILC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the adult, TrkA also acts as a pain receptor in sensory neurons and contributes to the transmission of pain signals to the central nervous system [8]. Outside of neuronal growth and pain signaling, there is an increasing number of studies demonstrating that TrkA tumour-promoting signaling is present in several human cancers, including those of the breast [10], oral cavity [11], thyroid [13], cervix [43] and lung [14,15]. In our study, TrkA protein expression was found preferentially in IDC as compared to DCIS and ILC.…”
Section: Discussionmentioning
confidence: 99%
“…In the adult, where neurogenesis is largely reduced, TrkA acts as a pain receptor in sensory neurons and contributes to the transmission of pain signals to the central nervous system [8]. Interestingly, TrkA is also oncogenic and there is accumulating evidence for its overexpression and involvement in cancer progression [9][10][11][12][13][14], including in the form of TrkA fusion proteins as described in lung cancer [15]. Furthermore, TrkA is a therapeutic target in oncology and Trk inhibitors are being tested in several clinical trials [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry (IHC) was performed as described previously (23). Following deparaffinization and rehydration of the TMA slides using standard procedures, heat-induced epitope retrieval was carried out in a low-pH, citrate-based antigen unmasking solution (catalog number H-3300, Vector Laboratories, California, CA, United States) by a decloaking chamber (Biocare, West Midlands, United Kingdom) at 95 • C for…”
Section: Pancreatic Tissue Samples and Immunohistochemistrymentioning
confidence: 99%
“…Treatment of cancers presenting TrkA fusion proteins with selective Trk inhibitors resulted in a better prognosis [51,52]. Further, over-expression of the NGF specific receptor TrkA is considered a reliable index of tumorigenicity, invasiveness, and chemotherapy resistance in several types of squamous cancers [53].…”
Section: Neurotrophins In Cscs-driven Tumor Growthmentioning
confidence: 99%